Development of mesopore-containing CON-type zeolite with unique acidic and catalytic properties. Issue 13 (10th June 2020) - Park, Sungsik; Sato, Gakuji; Onozuka, Hiroaki; Tsutsuminai, Susumu; Koike, Masakazu; Kuroda, Kazuyuki; Gies, Hermann; Kondo, Junko N.; Yokoi, Toshiyuki
Abstract : Post-synthetic hydrothermal treatment in NH4 OH solution containing cetyltrimethylammonium bromide. Abstract : The development of the mesoporosity of zeolite frameworks is an effective method to enhance the catalytic performance in the methanol-to-olefin reaction. Mesopore-containing CON-type boroaluminosilicate zeolite was prepared by the alkaline treatment based on the post-synthetic hydrothermal treatment in NH4 OH solution containing cetyltrimethylammonium bromide. The change in the concentration of NH4 OH solution led to CON zeolites with different mesopore volumes. The effects of the NH4 OH concentration on the structural properties of the treated samples were investigated by XRD, N2 adsorption, SEM, TEM, and 11 B, 27 Al, and 29 Si MAS NMR analyses. In addition, in situ FTIR with pyridine and 2, 4, 6-trimethylpyridine as probe molecules was applied to investigate the acidic properties. In the methanol-to-olefin (MTO) reaction, the mesopore-containing CON-type zeolite showed a longer catalytic life than the parent zeolite. The enhanced catalytic properties could be attributed to the dual effects of the alkaline treatment on the porosity and acidity modification.